ANALISIS PERHITUNGAN NILAI TAMBAH PADA AGROINDUSTRI STROBERI (Studi Kasus Pada Pelaku Usaha Di Desa Pandanrejo, Kecamatan Bumiaji, Kota Batu) - Widya Fatmawati, Erlin (Viabel : Jurnal Ilmiah Ilmu-Ilmu Pertanian, 2020)
This study examines the value added strawberries are processed into food that is more economical. This research is important because one of the obstacles faced by entrepreneurs in selling strawberries, the fruit is easily damaged. The purpose of this reseach was describe the characteristics of entrepreneurs agro-industry and agro-industry to analyze value added strawberries. Doing agroindustrial strawberries means providing added value to the products processed strawberries oriented higher selling prices. With the processing of strawberries, is expected to provide additional revenue businesses. By using the analysis of the value added by Metode of Hayami, it can be concluded that the three preparations of strawberries, namely dodol strawberries, strawberry jam and strawberry juice, which has the highest added value is the strawberry juice.